Progress and prospects in the management of psoriasis and developments in phyto‐therapeutic modalities. Issue 3 (18th March 2019) - Daniyal, Muhammad; Akram, Muhammad; Zainab, Rida; Munir, Naveed; Shah, Syed Muhammad Ali; Liu, Bin; Wang, Wei; Riaz, Muhammad; Jabeen, Farhat
Abstract: The aim of this study is to review the efficacy of herbal and allopathic drugs used to manage and treat psoriasis. The review has been compiled using reference materials from major databases, Online Journals, Science Direct, Scopus, Open J Gate, Google Scholar and PubMed. Psoriasis is a common skin disease affecting 2–3% of the world's population. It is cosmetically debilitating and chronic disease, which occurs both in developing and developed countries. It can affect any part of the body, but the most common sites are the elbows, knees, and scalp. It is usually treated with synthetic medicine either given systematically or applied locally. The prescribed synthetic medicines used for the treatment of psoriasis are associated with severe side effects and complications, thus researchers around the world are trying to explore new, more effective, and safer drugs from natural resources. Medicinal plants are safe and efficacious, and most of the people all over the world rely on herbal medicine due to their easy availability, low cost, and efficacy for treating psoriasis. A number of medicinal plants having therapeutic potential with high efficacy are used in the treatment of psoriasis have been described. Moreover, studies should be conducted to isolate and investigate the mechanism of actions of phytochemicals responsible for anti‐psoriasis potential.